Non-Destructive Tests on Normal and High Strength Concrete - Lopes, Sérgio Manuel Rodrigues (2018)
One of the most important concrete properties for structural concrete design or re-design is the compressive strength. Furthermore, other important concrete properties can be derived from the compressive strength. This property is typically obtained by standardised crushing tests on cast cubes or cylinders. However, cast cubes or cylinders may not be available for testing and, therefore, alternative tests need to be considered. The most reliable alternative test is the core test, which needs specimens extracted from the structure. Obviously, this is a very destructive test and other less destructive tests have been developed and deserve some attention. Some of non-destructive or partially destructive tests were carried out by the authors on normal and high strength concrete and compared with cube/cylinder common tests and also with core tests. This paper presents results from this study. Test procedures and reliability of non-destructive tests are analysed and discussed. Conclusions are presented.